Karakteristik briket ampas tebu (bagasse) dari bahan perekat tepung beras ketan - Maulana Fansyuri; - Nurkholis; - Mikhratunnisa; Lalu Heri Rizaldi; - Ariskanopitasari (Universitas Muhammadiyah Mataram, 2023)
Energy requirements are increasing with the increased of human activities that use either fossil fuel or biofuel. Biomass can be utilised as an alternative energy source in the form of briquettes. This study aims to increase the utilization of bagasse through the manufacture of briquettes using glutinous rice flour as the adhesive. Research variables include moisture content, ash content, destruction index, burning time and calorific value. This study used a completely randomized design (CRD) with variations in the concentration of glutinous rice flour 20%, 30%, and 40%. The results showed that the water content ranged from 5.85% - 7.65%. Ash content ranged from 6.44 to 8.14%. The destruction index was 0.24 – 0.65%. the burning time was between 124.67 -155 minutes, and the calorific value produced from bagasse briquettes was 7069.8 – 9759.3 cal/gram. The calorific value tend to decreased as the concentration of the adhesive was increased